The psychology of teaching and learning music - McClellan, Edward R. (New York : Routledge, 2023)
"The Psychology of Teaching and Learning Music introduces readers to the key theoretical principles, concepts, and research findings about learning, and how these concepts and principles can be applied in the music classroom. Beginning with an overview of the study of teaching and learning, and moving through applying theory to practice, and reflective practice in the process of personal growth, this text focuses on music learning theories, behavioral approaches, cognitive, social-cognitive development, and constructive views of learning. It includes culture and community, learning differences, motivation, effective curricular design, assessment, and how to create learning environments, illustrated by practical case studies, projects, exercises and photos. Showing students how to apply the psychology theory and research in practice as music educators, this book provides a valuable resource for undergraduate and graduate music education students and faculty"--
Introduction. The Study of Teaching and Learning ; Becoming a Reflective Teacher -- Part I: Theories of Learning and Teaching Music. Behaviorism : Learning Theory and Applications to Teaching ; Cognitivism : Learning Theory and Applications to Teaching ; Social Learning Theory and Applications to Teaching ; Humanism : Learning Theory and Applications to Teaching ; Brain-Based Learning Theory and Applications to Teaching -- Part II: Theory Applied to Practice. Cognitive Approaches in Teaching and Learning ; Sociocultural Characteristics of Learning in the Music Classroom ; School Music Curriculum Design -- Part III: Applications to the Music Classroom. Effective Instructional Design ; Assessment and Evaluation in the Music Classroom.
Keywords: Music -- Instruction and study -- Psychological aspects; EDUCATION / Educational Psychology; EDUCATION / Teaching Methods & Materials / Arts & Humanities; PSYCHOLOGY / Developmental / Lifespan Development